PERANCANGAN COMPANY PROFILE CAFE RUMAH BAKO MELALUI MEDIA WEBSITE - DESFADLIANTO, Drs. Syafwan, M. Si., Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Café "Rumah Bako" is one of the culinary is mountain Payakumbuh ie youngest mountain. Founded in 2012 by Mr. Andika Ari Andhyka, café "Rumah Bako" is located at Jorong Talago, Nagari Taeh Bukik, Sub Payakumbuh. With mountains in the background a cool and treated to views of the city Payakumbuh of the youngest mountain heights. Promotion ever done only through one of the print media in the city of Padang with installation logo on the advertising page. Promotion done through the print media is not giving effect seknifikan to the café "Rumah Bako" therefore made designing company profile through media websites with the aim of promoting and introducing café "Rumah Bako" which has the advantage with a location in the mountains, because the website can reach all people and in this digital age it is easier to provide information that affects its utilization in order to achieve a goal. The design of the website as the main promotional media café "Rumah Bako", supported by the media support: t-shirts, aprons, calendars, mugs, cards, stickers, keychains, CD cover and CD label. The data analysis was supported by the SWOT method. This method be used because the lack of promotion or a proper introduction to the café "Rumah Bako".Keywords: Web Design, located in the mountains, Café "Rumah Bako”.